2017
DOI: 10.1002/aic.15994
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐aided design of ionic liquids as solvents for extractive desulfurization

Abstract: Although ionic liquids (ILs) have been widely explored as solvents for extractive desulfurization (EDS) of fuel oils, systematic studying of the optimal design of ILs for this process is still scarce. The UNIFAC‐IL model is extended first to describe the EDS system based on exhaustive experimental data. Then, based on the obtained UNIFAC‐IL model and group contribution models for predicting the melting point and viscosity of ILs, a mixed‐integer nonlinear programming (MINLP) problem is formulated for the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
142
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 85 publications
0
142
0
1
Order By: Relevance
“…In other words, even two small sets of cations and anions can give rise to a huge number of possible DSILs, making the experimental trial‐and‐error method unrealistic for DSIL design. Moreover, besides the C ∞ and S ∞ of DSILs, their physical and thermodynamic properties at specific conditions of interest should also be evaluated to identify practically attractive extraction solvents . In this context, a systematic DSIL design method is proposed as illustrated in Figure , which consists of four steps.…”
Section: Description Of the Dsils Design Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, even two small sets of cations and anions can give rise to a huge number of possible DSILs, making the experimental trial‐and‐error method unrealistic for DSIL design. Moreover, besides the C ∞ and S ∞ of DSILs, their physical and thermodynamic properties at specific conditions of interest should also be evaluated to identify practically attractive extraction solvents . In this context, a systematic DSIL design method is proposed as illustrated in Figure , which consists of four steps.…”
Section: Description Of the Dsils Design Methodsmentioning
confidence: 99%
“…For the separation of thiophene and n ‐octane, sulfolane is used as benchmark solvent for DSILs prescreening because it is regarded as one of the most efficient conventional solvents for this process . In the first step, 44 [C 1 ] 0.5 [C 2 ] 0.5 A, 139 C[A 1 ] 0.5 [A 2 ] 0.5 , and 33 [C 1 A 1 ] 0.5 [C 2 A 2 ] 0.5 of the initially covered ion identities of DSILs are recognized with higher Cm and Sm than those of sulfolane (Cm = 0.49, Sm = 17.68); in contrast, only 14 two‐ion ILs are retained based on the same requirement (see Figure ).…”
Section: Methods Application To the Thiophene/n‐octane Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Having the UNIFAC model available, the optimal IL for gas separation can be designed through a computer‐aided molecular design approach . Zhen et al have developed a UNIFAC‐IL model and found the optimal solvent for extractive desulfurization of fuel oils through computer‐aided IL design.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Recently, a few studies have been reported which employed the Aspen Plus to simulate the desulfurization process by ILs. [30][31][32][33] For example, Nancarrow et al, 32 used Aspen Plus to perform the process simulation and optimization of an industrial EDS with the [C n mim][NTF 2 ] series of ILs, and observed that such IL-based extraction as an intermediate treatment can reduce the S-content from 7000ppm to 50 ppm. Song et al, 33 employed Aspen Plus to identify the performance of the top ILs as extractants in EDS of the model gasoline fuel and observed that proposed technique can be easily extended to screen the favorable ILs for other practical applications of extraction.…”
Section: Introductionmentioning
confidence: 99%